CLINICAL EFFICACY COMPARATIVE EVALUATION OF THE TREATMENT METHODS OF COMBINED DEFECTS AND DEFORMITIES OF THE ZIGOMA AND ORBIT - Yu.V. Chepurnyi; D.M. Chernohorskyi; O.I. Zhukovtseva; A.V. Kopchak (Український стоматологічний альманах)
Introduction. Zigoma and orbital defects still become an actual problem of maxilla-facial surgery due to limited possibilities to precise restoration of their complex anatomy. Functional unity of zigoma and orbit in aspects of eyeball support and protection increases requirements to reconstructive precision. The total and subtotal defects are the most difficult for reconstruction when traditional methods of reconstruction demonstrate unconvincing efficiency. Complex anatomy of zigoma and orbit, as combination of convexities, depressions limited an application of free or vascularised bone transplants for precise 3D restoration of the face. Facing this, new possibilities of reconstructed were developed, based on CAD/CAM technologies. Application of patient specific implants (PSI), designed according personal anatomy of the patient and manufactured by additive technologies, open new modalities to reconstruction in orthognatic surgery, cranioplasty and others, demonstrated promising results. So, these achievements and experience possible could be implemented for zigoma reconstruction. The aim of the study was to evaluate and compare clinical efficacy of zigoma and orbital defect treatment with traditional methods of reconstruction.